Multiantenna Analog Network Coding for Multihop Wireless Networks - Ramesh Annavajjala; Amine Maaref; Jinyun Zhang (International Journal of Digital Multimedia Broadcasting)
This paper proposes a two-phase minimum mean-square-error bidirectional amplify-and forward (MMSE-BAF) relaying protocol to allow two sources exchange independent messages via a relay node equipped with multiple antennas. MMSE-BAF performs a joint linear MMSE filtering of the received signal after the multiple access phase before amplifying and forwarding the filtered signal using a single transmit antenna, possibly through a specific antenna selection procedure, during the broadcast phase. The proposed protocol extends upon the so-called analog network coding schemes in the literature in that it inherently exploits the multiple antennas at the relay station to reduce the noise enhancement typical of an AF protocol, and can also compensate for link imbalances between the relay and the sources and is agnostic to sources' modulation and coding schemes. We derive the instantaneous signal-to-noise ratio expressions for the received signal by the sources in the downlink and provide extensive link-level simulations for the MMSE-BAF protocol subject to both frequency flat and selective fading. Furthermore, we pinpoint the modifications to be incorporated into the IEEE 802.16e orthogonal-frequency-division multiple access (OFDMA) cellular standard (mobile WiMax) to enable support of multiantenna bidirectional communications and show that MMSE-BAF is a viable solution within that framework.